Managerial responses to the new market; a case study of the appliance industry. - Gampel, Dana Peta (My University, 1995)
This dissertation examines two socially significant effects of Eskorn's Electricity For All programme: The new market that emerges once electricity becomes accessible, and managerial responses to this new market within the appliance industry. The research question asks how and why management in the appliance sector responds to the new market's demands. In answering this question, the new market is initially assessed. I have shown who constitutes this market and that these consumers prioritise top-of-the-range appliances. I have expanded on Pierre Bourdieu's concept of the habitus and used this to uncover these explanations of the new market. These findings have emerged through content analyses, in-depth interviews, a group workshop and participant observation methods. The dissertation then examines how and why management respond in specific ways to these market demands. I have assessed, through the use of a case study, why and how Tek Corp. the market leader in the appliance industry - responds strategically to the new market. I have examined management's response by addressing structures and responses within both the production and consumption phases of the circuit of capital. This dissertation has found that new types of competition are emerging within the appliance industry as a result of responses to the new market. I have thus argued that by assessing both production and consumption and by using the concept of the habitus, holistic explanations about capitalist relations in the appliance industry emerge.
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Masters of Arts.
Keywords: Marketing -- South Africa -- Management.; Electric apparatus and appliances -- South Africa.